Approximation of classes of analytic functions by Fourier sums in the metric of the space L_p - Serdyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
Asymptotic equalities are established for upper bounds of approximants by Fourier partial sums in a metric of spaces L_p,1 ≤ p ≤ ∞ on classes of the Poisson integrals of periodic functions belonging to the unit ball of the space L_1. The results obtained are generalized to the classes of (ψ, β)-differentiable functions (in the Stepanets sense) that admit the analytical extension to a fixed strip of the complex plane.